Investigation of the mechanical, thermal, and acoustical behaviors of cotton, polyester, and cotton/polyester nonwoven wastes reinforced epoxy composites. (January 2022) - Baccouch, Wafa; Ghith, Adel; Yalcin-Enis, Ipek; Sezgin, Hande; Miled, Wafa; Legrand, Xavier; Faten, Fayala
The aim of this paper is to develop a textile waste-based composite material with adequate mechanical, acoustical, and thermal properties for automotive or construction fields. For this purpose, three recycled nonwoven wastes including cotton, polyester, and cotton/polyester blend are employed and blended in epoxy resin. The manufacturing of the composite panels is performed by vacuum infusion technique. Mechanical, thermal and acoustical tests are conducted to characterize the performances of both nonwoven fabrics and composite panels. Theoretical Young's moduli of different composites are calculated based on the rule of mixtures in two ways and compared with practical results. Results show that mechanical properties of the manufactured panels are significantly improved compared to pure resin without a notable change in the thermal behavior of the epoxy resin, where composite reinforced cotton nonwoven shows a specific Young's modulus of 3500 MPa/g·cm −3 and a specific tensile strength of 38 MPa/g·cm −3 . These panels have been found to be promising materials to decrease the noise emission and good alternatives to pure epoxy products due to their contribution to reducing the textile wastes in landfills as well as the production costs.